Revised estimates of foetal and post-natal growth in young gray whales (Eschrichtius robustus) - Sumich, James L.; Blokhin, Sergey A.; Tiupeleyev, Piotr A. (J. Cetacean Res. Manage., 2023)
Patterns of gray whale growth in body length and weight with age are evaluated using published values of foetal and post-natal body dimensions at reported ages, supplemented with previously unpublished measured lengths of 88 mid-gestation foetuses, 82 first-summer calves and 30 secondsummer whales taken in the summer/autumn Chukotkan native subsistence fishery. Gompertz growth models are fitted to foetal and post-natal lengths at age, predicting mean lengths at birth in mid-January of 4.7m, 7.9m at weaning and 8.7m at one year. The late foetal diapause in growth of length is not supported by the available data. Two equations were derived for estimating body weights from the linear body dimensions of length and maximum girth. For biomass estimates, two equations based on length alone and on both girth and length are derived. A multiple least squares regression equation fit to 14 measurements of the same whale over 14 months of captive rehabilitation predicts mean body weights at birth of 1,100–1,200kg, 5,100–5,200kg at six months (weaning), and 6,700–6,800kg at one year of age.